"Dancing on the Brink of the World": Seeing Indigenous Dance and Resilience in the Archaeology of Colonial California. Issue 1 (26th November 2020) - Schneider, Tsim D.
ABSTRACT: In California, Indigenous hinterlands served as places of opportunity and safe harbor for Native people responding to colonization during the Mission Period (1769–1830s) and afterward. Even as Native communities visited Spanish missions in the San Francisco Bay Area, their long‐standing traditions of mobility supported novel opportunities to depart missions and seek out seasonally available foods. Hinterlands also provided contexts for Native people to conduct other social practices threatened by missionary colonialism. These were places to meet, mourn, dine, and dance. Expanding the Indigenous hinterlands concept, this article addresses the persistence of Indigenous dances. After reviewing the historical record of Native dances in California—simultaneously permitted/documented and forbidden/ignored within mission settings—I examine the archaeology of dances. Evidentiary priorities in archaeology and limited exploration of hinterland settings have impaired the study of where and how colonized people practiced their cultures. By paying closer attention to dance practice and the epistemological gaps in archaeology, Indigenous communities and archaeologists might further enhance studies of postcontact resilience and change and move closer to a decolonized archaeology. [ dance, archaeology, colonialism, Indigenous peoples, California ] RESUMEN: En California, los territorios indígenas interiores sirvieron como lugares de oportunidad y puertos seguros para los nativos respondiendo a la colonización durante el Período de las Misiones (1769–1830s) y después. Aún cuando las comunidades nativas visitaron las misiones españolas en el área de la Bahía de San Francisco, sus tradiciones bien establecidas de movilidad apoyaron oportunidades novedosas para salir de las misiones y buscar alimentos disponibles estacionalmente. Los territorios del interior también proveyeron contextos para los indígenas conducir otras prácticas sociales amenazadas por el colonialismo misionero. Estos fueron lugares para encontrarse, hacer duelo, comer y danzar. Al expandir el concepto de territorio interior indígena, este artículo aborda la persistencia de las danzas indígenas. Después de revisar el registro histórico de las danzas nativas en California –simultáneamente permitidas/documentadas y olvidadas/ignoradas dentro de los contextos de la misión– examino la arqueología de las danzas. Prioridades probatorias en arqueología y exploración limitada del contexto de los territorios interiores han impedido el estudio de dónde y cómo las personas colonizadas practicaron sus culturas. Al poner atención más cercana a la práctica de la danza y los vacíos epistemológicos en arqueología, las comunidades indígenas y los arqueólogos podrían mejorar aún más los estudios de la resiliencia postcontacto y cambio, y moverse más cerca a la arqueología descolonizada. [ danza, arqueología, colonialismo, Indígenas, California ]